2020
DOI: 10.1177/1178221820909354
|View full text |Cite
|
Sign up to set email alerts
|

The Good, the Bad, and Recovery: Adolescents Describe the Advantages and Disadvantages of Alternative Peer Groups

Abstract: In 2017, approximately 1.5 million American adolescents had a substance use disorder (SUD). Adolescents with SUD risk hindering their neurological development, which can result in problems with memory and self-regulation, and in turn disrupt their education, relationships, and life opportunities. Treating adolescents with SUD is challenging. Thus, effective models that help adolescents engage in long-term recovery are needed. The Alternative Peer Group (APG) is an adolescent recovery support model that incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Becker et al (2017) also found that the environment and positive or negative experiences can also influence the brain and affect vulnerability to drug addiction among males and females. Smith et al (2020) also argued that adolescents at SUD risk had hindered neurological development, which can cause problems with memory and self-regulation, and in turn disrupt their education, relationships, and life opportunities. National Institute on Drug Abuse (2020) explains that for teens, using substances when the brain is still developing may cause lasting brain changes and put the users at increased risk of dependence.…”
Section: │ 179mentioning
confidence: 99%
“…Becker et al (2017) also found that the environment and positive or negative experiences can also influence the brain and affect vulnerability to drug addiction among males and females. Smith et al (2020) also argued that adolescents at SUD risk had hindered neurological development, which can cause problems with memory and self-regulation, and in turn disrupt their education, relationships, and life opportunities. National Institute on Drug Abuse (2020) explains that for teens, using substances when the brain is still developing may cause lasting brain changes and put the users at increased risk of dependence.…”
Section: │ 179mentioning
confidence: 99%
“…While intervention research highlights the importance of avoiding or reducing situations in which high-risk behaviours such as substance misuse or criminal behaviour can be mutually reinforced through peer feedback [166][167][168], the positive effects of social context and positive peer influence on behaviour should not be overlooked [112,113,[169][170][171]. Interventions that mitigate the social risk of peer ostracisation and facilitate the creation and support of positive peer groups for adolescents may be particularly effective in promoting prosocial, healthy behaviour [172]. Adolescent's heightened sensitivity to peer influence can also be harnessed as a driver of positive behavioural change.…”
Section: M Pl Ications Of a Dol E Sce N T N Eu Rocogn Iti V E Dev E L...mentioning
confidence: 99%
“…Previous studies have documented many types of risk factors. Among these are peer influence, stress, developmental changes, and negative role models (Roblyer, Betancourth & Grzywacz, 2015;Smith, Vasquez, Emelogu, Hayes, Engebretson, & Nash, 2020;Tam, Kwok, Lo, Lam & Lee, 2018). Besides, discrimination, ethnic identity, access to drugs, and misperceptions about the risk of drugs (Verissimo, Gee, Ford, & Iguchi, 2014;Zapolski, Clifton, Banks, Hershberger, & Aalsma, 2017) have also been identified as risk factors.…”
Section: Introductionmentioning
confidence: 99%